The state of human capital in the field of Science and Innovations in Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2017)
This paper analyzes the status and use of the human capital of Kazakhstanin the field of science and innovation as a competitive advantage ofthe economy, and the possibility of upgrading to a large extent determinedby the accumulated and implemented human capital, which is one of themain factors for the accelerated innovative development of the country.Theoretical material about the importance and priority of human capital foreconomic development was studied. The relevance of the topic was justifiedby the need of formation and development of new approaches and newconditions for training and upgrading scientific and technological capacity.The education, skills and experience of people define the limits and possibilitiesof technological, economic and social modernization of society. Thepaper evaluated the existing scientific and technical capacity, the reasonsof relatively low innovation activity of enterprises in Kazakhstan and suggestedmeasures for successful innovation oriented type development. Theconducted analysis of the state and the use of human capital in the field ofscience of the Republic of Kazakhstan shows that human capital needs to begiven due attention as a factor of innovative development.